Rationalization of Teachers’ Behavioral Expectations from Secondary School Girls in Lahore: A Phenomenological Study - Syeda, Shaista; Saleem, Mehek; Ashfaq, Muhammad (Annals of Human and Social Sciences, 2023)
The focus of this article is to understand the gender-based socio-cultural attributes which influence teachers’ expectations from high school female students in their classrooms and schools. For the purpose, qualitative phenomenological research was designed to understand the differences between single-sex and coeducation school teachers’ behavioral expectations from secondary school girls. Two teachers of single-sex and two teachers of coeducation school system participated in detailed open-ended interviews. The findings suggested that teachers’ own academic experiences as a student influenced their perceptions and expectations from secondary school girls. The gender-neutral expectations of teachers largely depended upon their critical reflection on their own experiences that they had when they were studying in schools. The in-service teacher training focused on critical reflection on teachers’ social and cultural gender related experiences will help the teachers to identify gender-based expectation from students as well as to learn the strategies to maintain a more inclusive academic environment.